Online Customer Engagement: A Systematic Literature Review using PRISMA protocol (International Journal of Scientific Research and Management (IJSRM), 2024)
Customer engagement (CE) is a crucial marketing concept whose relevance has been further enhanced by the growth of social media and digital marketing. While the significance of CE is widely recognized, the research in this domain is notably fragmented, characterized by diverse definitions and conceptualizations found in the literature. This fragmentation raises concerns, as the absence of standardization may result in misunderstanding and contribute to increased divergence in future research. This paper presents a systematic review of customer engagement using PRISMA protocol by delivering its antecedents, outputs, and influencing factors. We focus on three main features: the relationship quality (i.e., trust, satisfaction, and commitment), the channel integration quality, and digital transparency. As a result, we provide hypotheses of a micro-level conceptual model for customer engagement. We also highlight the adoption of technological innovation (e.g., Artificial Intelligence, Machine Learning, GhatGPT) to foster online customer engagement.